An industrial quality control study on IDS Logistics (involving Unilever Food Solutions Products) - Guarin, Andrei (Quezon City College of Engineering, University of the Philippines Diliman, 2006)
In order to apply the statistical process control methods learned in IE 135, the group undertook a study on a company with certain methods and processes that needed to be monitored. Unilever Foods (formerly known as California Manufacturing Company or CMC), an already-established company in the Philippines, was chosen as the site, and the group was assigned to work specifically on the product lines of Best Foods Say Cheeez and Lady's Choice Mayonnaise. These products are manufactured in Unilever's main plant located in Gateway Industrial Park in General Trias, Cavite, and thus the company relies on Integrated Distribution Systems (IDS) Logistics for its transportation and warehousing needs. The group chose to utilize the P attributes control chart, since no measurement is involved in inspecting the products; these are only observed as in good condition (conforming) and damaged or with discrepancies (non-conforming). Analyzing the data gathered, it can be seen that the problems indicated indeed pose a problem for both IDS and Unilever, since these consistently interrupt the flow of products from the principal (Unilever) to the warehouse (IDS) and to the clients. Aside from incurring time/production delays due to product repacking, re-labelling and complete product replacement, the company also incurs additional costs with regards to manpower and material. With regards to the problems of damaged cartons, collapsed cartons and wet cartons, these can be traced to the trucks involved and driver handling. Since one hundred percent inspection is done as well on the pallets (by Unilever personnel) before the products leave the Gateway plant, most the damages incurred by the cartons are traced to in-transit reasons, some (ie Wrong BB Dates) to errors in inspection. Product leakages can be attributed to product packaging within the Unilever compound, since packaging for each variant is designed such that leakages during product transport are minimized/ eliminated. Oil separations happen when too much heat is absorbed by the mayonnaise package, causing the product oil to separate from the other ingredients. Damaged cartons were found to be the most prominent problem among the 6 nonconformities, and it can also be observed that 5 out of these 6 can be classified as due to physical occurrences on the cartons/pallets. Proper loading and securing of these products during transport are key preventive measures by which the number of nonconforming arrivals can be reduced. The group recommended that either a full plastic cover or a tarpaulin cover on the products be used inside the truck. Either one will prevent minor shakes on the products, as well as serve as a shield from rainwater seeping into the truck's cargo area. A time study was also recommended by the group to be conducted on Unilever's packaging area, since bottlenecks are currently present. Reduced waiting time by the finished products in the packaging area will mean reduced exposure time, and will in turn lessen the risk of damage and of oil separations (especially in the case of the 3.5L variants).
"This project was conducted by Andrei Guarin, Eugene Rex Jalao, Janine Lei Quizon, and Christopher Ian Ulpindo in the first semester of schoolyear 2005-2006 under Ms. Erika R. Oberio, and has been re-edited for submission. The original project report contained an FMEA study on the delivery process, which has been revised and submitted as a separate FMEA Case as well."
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial quality control.
Keywords: Unilever Philippines; Condiments; Business logistics; Quality control